2016
DOI: 10.1523/jneurosci.0148-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Is Required for Endothelial Cyp1b1 Regulation Influencing Metabolic Barrier Function

Abstract: The canonical Wnt/␤-catenin signaling pathway is crucial for blood-brain barrier (BBB) formation in brain endothelial cells. Although glucose transporter 1, claudin-3, and plasmalemma vesicular-associated protein have been identified as Wnt/␤-catenin targets in brain endothelial cells, further downstream targets relevant to BBB formation and function are incompletely explored. By Affymetrix expression analysis, we show that the cytochrome P450 enzyme Cyp1b1 was significantly decreased in ␤-catenin-deficient mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…cyp1b1 was shown to be one of the most highly expressed CYP enzymes in human brain microvessels from patient biopsies [ 43 ]. More recently it was shown that B-catenin positively regulates cyp1b1 , but not cyp1a1 , in endothelioma cell lines [ 44 ], and the authors concluded that the ability of cyp1b1 to synthesize retinoic acid (from retinol) and 20-HETE (from arachnidonic acid) were essential in modulating BBB function. Furthermore, this study demonstrated that B-catenin was required for the AHR-dependent induction of cyp1b1 expression by TCDD.…”
Section: Discussionmentioning
confidence: 99%
“…cyp1b1 was shown to be one of the most highly expressed CYP enzymes in human brain microvessels from patient biopsies [ 43 ]. More recently it was shown that B-catenin positively regulates cyp1b1 , but not cyp1a1 , in endothelioma cell lines [ 44 ], and the authors concluded that the ability of cyp1b1 to synthesize retinoic acid (from retinol) and 20-HETE (from arachnidonic acid) were essential in modulating BBB function. Furthermore, this study demonstrated that B-catenin was required for the AHR-dependent induction of cyp1b1 expression by TCDD.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that differentiating hPSC‐derived BMECs respond to all‐trans retinoic acid (RA), a hormone implicated in CNS development and hindbrain patterning and BBB development. Previous studies have identified RA production by astrocyte progenitor cells during embryonic BBB development and coordination with WNT signaling to promote BBB fidelity . During hPSC differentiation to BMECs, administration of RA during the EC expansion phase (D6–D8) and the first 24 h of the subculture phase (D8–D9) induced VE‐cadherin expression at D8, and the resulting BMECs exhibited dramatically elevated transendothelial electrical resistance (TEER) at D10 of the differentiation, an indicator of BMEC barrier function .…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of ECs with the permeability-inducing factor thrombin induced the translocation of p120-catenin and β-catenin into the nucleus and the expression of β-catenin target genes, which indicated that the binding of p120-catenin and β-catenin to the AJ complex may reduce the signaling pathways of these molecules. Multiple studies suggest the role of β-cateninmediated Wnt transcription in EC biology and vascular development [39,40]. We demonstrate that β-catenin plays an important role in maintaining endothelial homeostasis.…”
Section: Discussionmentioning
confidence: 63%